A new spectrophotometric method based on peroxidase enzymatic reaction to determine tetracycline in pharmaceutical and water samples - Sam ang Supharoek (2020)
© 2020, Iranian Chemical Society. An enzymatic method for cost-effective and reliable spectrophotometry was described based on the catalytic reaction of peroxidase enzyme to detect and determine tetracycline. Daikon (Raphanus sativus L.), a local vegetable, was exploited as a source of peroxidase enzyme, extracted by a simple method and utilized for tetracycline detection without any purification steps. A blue color product which absorbed maximal wavelength at 600 nm was observed when mixing tetracycline, 4-aminoantipyrine and hydrogen peroxide in the presence of daikon peroxidase under pH 7.5. Parameters influencing the proposed method as pH, concentration of hydrogen peroxide, concentration of 4-aminoantipyrine, volume of crude enzyme extract, incubation temperature and incubation time were investigated and optimized. Cloud-point extraction using Triton X-114 as surfactant was employed for preconcentration of the blue color product prior to spectrophotometric analysis. The calibration curve of standard tetracycline showed good linearity in the range 0.05–10 mg L−1 with linear regression of r2 = 0.9982. Limit of detection and limit of quantification for tetracycline by this analytical method were 0.02 and 0.10 mg L−1, respectively. Relative standard deviation was lower than 5%. Recovery was determined between 81.1–112.8 and 97.2–114.8% for pharmaceutical formulations and water samples, respectively. Results indicated that the developed method provided many advantages including a cost-effective, suitable and reliable procedure to detect tetracycline in pharmaceutical formulations and water samples. Results obtained were not significantly different from those achieved by HPLC–UV.